EFEKTIVITAS POSISI TANGAN PENOLONG DALAM PENCEGAHAN RUPTUR PERINEUM SPONTAN PADA KALA II PERSALINAN DI RSIA â€œBunda arifâ€ PURWOKERTO TAHUN 2013 - Priyantini, Mulyati; Agustina, Ely Eko (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
Main focus of delivery care is preventing the complication to reduce the maternal morbidity and mortality. One of the efforts to prevent the occurance of perineal rupture. The position hand which is used birth attendant in the second stage of labor to prevent perineal rupture among others APN and Varney hands position. This reasearch was observational analytic by approachment cross sectional with population of this reasearch was all of spontaneous delivery in RSIA ‘Bunda arif’ Purwokerto and the sample used quota sampling, it’s about 30 sample can be a inclusion criteria. The analyze method data used U Mann-Whitney test. The known result : 1) Precentage of spontaneous perineal rupture by APN hand position is 93,3%, 2) Precentage of spontaneous perineal rupture by Varney is 86,7%, 3) statistic analysis used U Mann-Whitney test is p value = 0,550 (p>0,005) and U value = 33,000 (Uh < U t). It means, not significant difference, but Varney hands position better by a margin of 6.6%. Varney hands position is more effective than APN hands position in prevention spontaneous perineal rupture in the second stage of labor, but both not significant for perinel rupture. Keyword : APN & Varney hands position, and perineal rupture.